Differences in Inflammatory Parameters of Child-Pugh B and Child-Pugh C Scores of Liver Cirrhosis with Hepatorenal Syndrome - Panggabean, Lider Olmen; Siregar, Gontar Alamsyah; Lubis, Masrul (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Background: Child-Pugh score is used to predict the poor prognosis of liver cirrhosis patients. The study objectives analyzed differences in inflammatory parameters of Child-Pugh B and Child-Pugh C of liver cirrhosis with hepatorenal syndrome. Method: Desain's study is cross-sectional in liver cirrhosis patients with hepatorenal syndrome.Â This research was approved by the Health Research Ethics Commission FK USU / RSUP H. Adam Malik Medan and meets the criteria of inclusion or exclusion. Diagnosis of Liver cirrhosis Child-Pugh B and Child-Pugh C score is done by clinical examination, laboratory, and ultrasound, CT scan, MRI. The hepatorenal syndrome was diagnosed using Criteria International Ascites Club, 2007. Results: The sample number of this study was 26 liver cirrhosis with hepatorenal syndrome patients consisting of Child-Pugh B patients 9 patients and Child-Pugh C patients 17Â patients. The comparison between Child-Pugh B and Child-Pugh C has significant differences in leukocyte, Na, Cl, SGOT, and CTP. There is a significant correlation between CTP and leukocytes, platelets, Cl, creatinine, GFR, albumin, total bilirubin, and glued bilirubin. Conclusion: There is no clear difference in the inflammatory parameters of the Child-Pug B and Child-Pug C scores in liver cirrhosis with hepatorenal syndrome.